Revitalisasi BUMDes Waterboom Tirta Mulya: Upaya Pemberdayaan Ekonomi Desa Sumber Mulya melalui Pengembangan Sektor Pariwisata Berkelanjutan - M. Anwar Rifa'i; Nandang Syamsul Arifin; M. Nur Tanjali (Jurnal Pengabdian Masyarakat: Tipis Wiring, 2025)
This community service program focuses on the revitalization of BUMDes Waterboom Tirta Mulya in Sumber Mulya Village, a transmigration village in South Sumatra. The program aims to revive the village's tourism potential, which was halted due to the COVID-19 pandemic. Through a series of activities such as cleaning and repairing facilities, filling and purifying the pool water, and promoting through social media, the program has successfully prepared the waterboom to reopen. The positive impacts include an increase in Village Original Income (PAD), creation of new job opportunities, and empowerment of the community in managing the tourism business. Additionally, this program has also provided positive environmental impacts, such as improved cleanliness and increased community awareness of environmental preservation. In conclusion, the revitalization of the waterboom not only provides short-term economic impacts but also strengthens community empowerment and the sustainability of tourism in Sumber Mulya Village. Recommendations are given to continue improving the management of the waterboom through community training and ongoing promotion to achieve greater economic and social impacts.